Oligomerization of propene over ZSM-5 modified with Cr and W (2011)
ABSTRACT: In this paper, the composition of ZSM-5 was modified with Cr and W by impregnation, isomorphous substitution and ion exchange, and the resulting catalysts were evaluated in the oligomerization of propene.